Ferramentas de modelagem espacial aplicadas à avaliação da qualidade da água subterrânea na área urbana do município de Passo Fundo-RS - Bagnara, Daniela (2010)
The study of groundwater quality through spatial modeling is of considerable importance for the management of water resources. In this context, the objective of the present study was to evaluate the potential use of geostatistical modeling techniques and tools to characterize the spatial dispersion of the main parameters that define groundwater quality, in terms of its drinkability, in the urban area of Passo Fundo/RS. In general, the geostatistical methodology provides a body of statistical tools that quantify the spatial continuity of a variable in study, from the application of mathematical interpolation models, based on the structural variability of a spatial phenomenon, and stochastic simulation models, which allow the quantification of the uncertainty associated with the interpolated values (estimates). The spatial phenomenon studied in the present work was restricted to a discrete and limited set of 127 deep wells and the respective available data on physical-chemical and microbiological characteristics of groundwater. These dataset was obtained from the Municipal Health Department and a deep well construction company located in Passo Fundo/RS, for a period of 5 years. Through the implementation and evaluation of geostatistical predictive methods, such as ordinary kriging and indicator kriging, it was possible to preliminarily characterize the spatial distribution and continuity of the groundwater quality in the study area. The results enabled the evaluation and comparison of different geostatistical methods and also the establishment of technical criteria and guidelines for implementing a groundwater quality monitoring program in the city of Passo Fundo/RS